2016
DOI: 10.1109/tns.2016.2517739
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Studies With BGO Scintillators Coupled to Low-Noise, Large-Area, SiPM Arrays

Abstract: Despite the fact that timing capabilities for devices based on BGO are limited when compared with LYSO or LSO based systems, the cost of BGO is considerably lower and could thus, be an option for devices with high scintillator volumes (as in the case of nuclear medicine scanners), but also in smaller dedicated imagers. Recently, many studies have been carried out in order to determine the potential capabilities of BGO for PET and SPECT applications, where BGO scintillator crystals have been coupled to SiPM pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The main motivation of this work is a new opportunity to build PET systems requiring large volume of scintillators at a moderate cost. We have recently showed the possibility of a dual-layer BGO block using crystal arrays [4]. Here, we have also demonstrated the possibility of using monolithic blocks achieving almost 5 mm FWHM in DOI resolution.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The main motivation of this work is a new opportunity to build PET systems requiring large volume of scintillators at a moderate cost. We have recently showed the possibility of a dual-layer BGO block using crystal arrays [4]. Here, we have also demonstrated the possibility of using monolithic blocks achieving almost 5 mm FWHM in DOI resolution.…”
Section: Discussionmentioning
confidence: 66%
“…Each row and column signal was charge integrated with a time gate of 600 ns (see figure 1 right for a signal example). We have already shown that this value is optimal for our data acquisition system [3,4]. This row-column readout approach makes it possible to characterize the scintillation X-Y light projections.…”
Section: Jinst 12 C11027mentioning
confidence: 91%
See 1 more Smart Citation
“…They were improved to 27%-30% with the DOI correction. The energy resolution in this study is worse than the energy resolutions of other BGO detectors with similar pitch (Zhang et al 2002, Gu et al 2013, González et al 2016, mainly due to the fact that the BGO elements used here that have unpolished lateral surfaces and Toray reflectors which provide good DOI resolution, however, reduce the number of scintillation photons reaching the SiPMs and shift the 511 keV photopeak as a function of depth (figure 10 (right)).…”
Section: Discussionmentioning
confidence: 71%